Relationship Between Lumbar Multifidus Morphometry and Pain/Disability in Individuals With Chronic Nonspecific Low Back Pain After Considering Demographics, Fear‐Avoidance Beliefs, Insomnia, and Spinal Degenerative Changes - Sabina M. Pinto; Jason P. Y. Cheung; Dino Samartzis; Jaro Karppinen; Yong‐Ping Zheng; Marco Y. C. Pang; Maryse Fortin; Arnold Y. L. Wong (JOR Spine)
ABSTRACT Background Although individuals with chronic low back pain (CLBP) show increased fatty infiltration in the lumbar multifidus muscle (LMM), it remains unclear whether LMM changes are related to clinical outcomes (such as pain and disability) after considering confounders (spinal phenotypes, fear‐avoidance beliefs [FABs] and insomnia). This study examined: (1) differences in confounders and LMM characteristics between individuals with and without CLBP; and (2) associations between confounders, LMM parameters, and clinical outcomes in the CLBP group alone. Methods Participants (CLBP = 70 and asymptomatic people = 67) underwent lumbar magnetic resonance imaging. Outcome measures comprised the numeric pain rating scale, the Roland–Morris Disability Questionnaire, the Fear‐Avoidance Beliefs Questionnaire (FABQ), and the Insomnia Severity Index (ISI) Scale. LMM morphometry at L3‐S1 (cross‐sectional area, total volume, and fatty infiltration) was measured using a customized MATLAB program. Spinal phenotypes (disc degeneration, high‐intensity zones, Modic changes [MCs], Schmorl's nodes, facet joint degeneration [FJD], and facet tropism [FT]) were scored. The between‐group differences were analyzed using linear mixed models and chi‐squared/Fisher's exact tests. Univariate and multivariate analyses evaluated associations between clinical outcomes and other outcome measures in the CLBP group. Results The CLBP group demonstrated more severe disc degeneration and FJD at all levels, and greater FT at L5/S1 than asymptomatic participants (p < 0.05). The average LMM total volume at L3/4 and the percentage of fatty infiltration in LMM in the L3‐S1 region were greater in the CLBP group than in asymptomatic counterparts (p < 0.05). The presence of MC at L4 and FJD at L4/5 and L4‐S1 was significantly related to pain intensity in the CLBP group. Similarly, FABQ‐Work and ISI scores were significantly related to pain intensity (explaining 37% of the variance in pain). Conclusions The CLBP group displays more fatty infiltration in the LMM, but their LMM morphometric parameters are unrelated to pain/disability after considering spinal phenotypes, FABs, and insomnia.